A study to find out correlation between clinical diagnosis and histopathological diagnosis in patients with acute appendicitis undergoing surgical treatment - Jain, Mohit; Sharma, Yogesh Kumar (International Surgery Journal, 2019)
Background: Acute appendicitis is one of the most frequent abdominal emergencies and appendectomy subsequently the most common emergency operation performed all over the world. The aim of the study is to evaluate the reliability of Clinical Diagnosis for diagnosis of acute appendicitis and correlate it with the gold standard and absolute diagnostic modality, histopathology. Methods: This is a prospective study carried out in 150 patients who were admitted under department of surgery, AFMC Pune, Maharashtra from 1st July 2014 to 31st June 2016 for a clinical diagnosis of acute appendicitis. Results: In our study overall negative appendectomy rate was 18.7% (12.37% in male and 30.19% in female). Hence in the overall females had more negative appendectomy rate compared to males. In our series a score of >7 using Alvarado system had a total sensitivity of 72.95%. While sensitivity increases to 99.18% when score of >5 used as cut-off. Conclusions:Alvarado scoring system is beneficial in decreasing negative appendectomy rate and thus reduces complication rates. It is effective in the diagnosis of acute appendicitis in both men and females but some other diagnostic modality may be necessary to ascertain the diagnosis in females along with the clinical scoring system to rule out other pelvic pathology and to reduce negative appendectomy rate in females.